2018
DOI: 10.3389/fbuil.2018.00035
|View full text |Cite
|
Sign up to set email alerts
|

Far-Field Earthquake Responses of Overhead Line Equipment (OHLE) Structure Considering Soil-Structure Interaction

Abstract: Overhead line equipment (OHLE) is the components for the electric train which supply the electric power to the train. For one or two tracks, OHLE is normally supported by cantilever mast. The cantilever mast, which is made of H-section steel, is slender and has a poor dynamic behavior by nature. Nonetheless, the mast structures, which located alongside the railway track, have not been fully studied on the dynamic behavior. This paper presents the effects of far-field excitations on cantilever mast and overhead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…It was clearly shown that the placement of the viscous dampers plays an important role in reducing the acceleration response. In addition, the optimal damping effect can be achieved by optimizing the parameters of the viscous dampers, similar to other researches [30][31][32][33][34].…”
Section: Appl Sci 2019 9 X For Peer Reviewmentioning
confidence: 75%
“…It was clearly shown that the placement of the viscous dampers plays an important role in reducing the acceleration response. In addition, the optimal damping effect can be achieved by optimizing the parameters of the viscous dampers, similar to other researches [30][31][32][33][34].…”
Section: Appl Sci 2019 9 X For Peer Reviewmentioning
confidence: 75%
“…A is the roughness constant ( As the most efficient infinite boundary, perfectly matched layers (PML) method is used to prevent spurious wave reflections from the truncated boundary [32,33,34,35,36,37]. while the left side of ground has the same mesh but with ground soils inside.…”
Section: Modeling Of the High-speed Train And Slab Trackmentioning
confidence: 99%
“…Special thanks to European Commission for H2020-MSCA-RISE Project No. 691135 "RISEN: Rail Infrastructure Systems Engineering Network" (www.risen2rail.eu) [43]. In addition, the collaboration and assistance from EU Cost Action TU1404 (Towards the next generation standards for service life of cement-based materials and structures) is highly appreciated.…”
Section: Acknowledgmentsmentioning
confidence: 99%